Clinical researches on the efficacy of spa therapy in fibromyalgia: a systematic review - Antonio Fraioli; Marcello Grassi; Gioacchino Mennuni; Andrea Geraci; Luisa Petraccia; Mario Fontana; Stefano Conte; Angelo Serio (Istituto Superiore di Sanità, 2013)
BACKGROUND: Fibromyalgia is characterized by chronic widespread pain, tenderness at muscle and tendon insertions point when digital pressure is applied, sleep disorders, chronic fatigue, depressive episodes, anxiety, and other functional somatic syndromes. OBJECTIVE: The aim of this study was to determine whether balneotherapy with mineral waters and mineral-water containing mud is effective in the management of fibromyalgia. METHODS: We conducted a systematic review of the literature regarding spa therapy in the treatment of the fibromyalgia. We searched many databases for articles published between 2000 and 2012 and we selected 7 studies among 65 articles retrieved. A total of 142 patients received balneotherapy and 129 were controls. CONCLUSIONS: Study data confirms that spa therapy could improve the symptoms of fibromyalgia including pain, depression and minor symptoms.